QUANTIFYING WINDOW EFFECTIVENESS TO AFFECT WIND VELOCITY BY EXPERIMENTAL STUDY - Intan Findanavy Ridzqo; Estuti Rochimah; Jerrino Soedarno (Universitas Mercu Buana, 2021)
Particular ventilation design can create effective natural air movement into the indoor environment by flowing the outside wind. The window, as a kind of ventilation, has various designs. It combines three primary constructions: simple opening, vertical-pivot, and horizontal-pivot opening. Each has a particular characteristic to control air velocity and direction which flows through it. However, the wind is not always certain in the mean of its velocity and direction, which heavily relies on the season. This study is written to investigate the single window’s performance by measuring its effectiveness to control wind velocity in some directions. The effectiveness is conceived as a percentage rate that a window could maintain the outside wind velocity when it flows through the window. This experimental study employs three factors that are wind direction, window design and opening angle. This study operated 1:1 model of ten window designs, a simulation wall, and an electric fan to generate the Building Physics Laboratory's intended wind in the Department of Architecture, Institut Teknologi Indonesia. The result shows that maximum opening angle with perpendicular wind is the most effective situation to flow wind through all window—except simple casement window—with the rate ranging at 85,16% – 123,76%. The wind could also be more speeded up 109,63% – 193,90% when it aligned to all windows. Simple casement window even reaches 266,22% when the wind perpendicular.